2-Keto-3-Deoxygluconate 6-Phosphate Aldolase Mutants of Escherichia coli - Fradkin, Judith E. (1971)
A new mutation in Escherichia coli, giving inability to grow on gluconic, glucuronic, or galacturonic acids, has been identified as complete deficiency of 2-keto-3-deoxygluconate 6-phosphate (KDGP) aldolase activity. The genetic map position of the locus, eda, is about 35 min. The inability to grow on the uronic acids was expected, because the aldolase is on the sole known pathway of their metabolism. However, inability to grow on gluconate was less expected, because the hexose monophosphate shunt might be used, as happens in mutants blocked in the previous step, edd, of the Entner-Doudoroff pathway. The likely explanation of gluconate negativity is inhibition by accumulated KDGP, because gluconate is inhibitory to growth on other substances, and one type of gluconate revertant is eda(−), edd(−). KDGP is probably the inducer of KDGP aldolase.